Catch composition of fishes by different types of fishing gears in the Andaman sea, Thailand - Ananya Jarernpornnipat; Thanyaporn Pongsuwan; Kathe R. Jensen (Brazilian Journal of Development, 2024)
The Andaman Sea is a rich ecosystem providing significant ecosystem goods and services for people in coastal areas and these areas have fisheries activities using different fishing gears appropriate for different species and habitats. We assessed catch composition and size distribution of economically important finfish captured by a range of fishing gears employed by commercial and artisanal fishers in three provinces adjacent to the central Andaman Sea of Thailand over a 2-year period. Between January 2019 and December 2021, fishers employed 7 main capture gears: surface gillnet, bottom gillnet, fish trap, handline and hook, trawl, purse seines and light-luring anchovy falling net. Trawling captured the highest diversity of target species (35 species) followed by surrounding net (32 species), fish trap (16 species) hook and line (15 species), surface and bottom gillnet (15 species) and the last one of anchovy falling net (2 species). When comparing size at the first maturation of both target species and bycatch, it was found that the percentage of mature fish caught from artisanal fishing gears was higher than of commercial fishing gear because artisanal gears had better selection of catch, especially fish trap and hook and line. Understanding the operation of fishing gears, catch composition and the size frequencies of target species could be particularly important for stock assessment because gear may influence catch composition.
Keywords: Fish Biology and Ecology Studies; Marine and fisheries research